Mutational analysis of conserved glutamic acids of Pho89, a Saccharomyces cerevisiae high-affinity inorganic phosphate:Na+ symporter - Andersson, Michael R; Samyn, Dieter R; Persson, Bengt L (Biológia, 2012)
In Saccharomyces cerevisiae, the high-affinity phosphate transport system comprises the Pho84 and Pho89 permeases. The Pho89 permease catalyzes import of inorganic phosphate in a symport manner by utilizing Na+ ions as co-solute. We have addressed the functional importance of two glutamic acid residues at positions 55 and 491. Both residues are highly conserved amongst members of the inorganic phosphate transporter (PiT) family, which might be an indication of functional importance. Moreover, both residues have been shown to be of critical importance in the hPit2 transporter. We have created site-directed mutations of both E55 and E491 to lysine and glutamine. We observed that in all four cases there is a dramatic impact on the transport activity, and thus it seems that they indeed are of functional importance. Following these observations, we addressed the membrane topology of this protein by using several prediction programs. TOPCONS predicts a 7-5 transmembrane segment organization, which is the most concise topology as compared to the hPiT2 transporter. By understanding the functionality of these residues, we are able to correlate the Pho89 topology to that of the hPiT2, and can now further analyze residues which might play a role in the transport activity.